PENGARUH PEMBINAAN BERBASIS ASRAMA DAN RELIGIOSITAS TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM BAGI PESERTA DIDIK - Aziqra, Miftah Fatiah; Al Ghifarry , Ubaidillah; Pahrurraji (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
This research aims to examine the influence of dormitory-based coaching and religiosity on Islamic Religious Education (PAI) learning outcomes at SMP AQL Islamic School (AQLIS) Jonggol, West Java. The method used is ex-post facto with a sociological and psychological approach. The research population consisted of 123 male students, with a sample of 54 informants selected by purposive and random sampling, including school principals, high achieving students and non-achieving students. Data was collected through questionnaires and documentation, and validated with internal and external validity and Cronbach's Alpha reliability. Data analysis was carried out descriptively and inferentially, including normality, homogeneity, linearity tests, and hypothesis testing using product moment correlation and simple linear regression. The research results show that dormitory-based coaching and religiosity have a significant influence on student PAI learning outcomes at AQLIS Middle School. Structured dormitory development and increasing student religiosity have been proven to contribute positively to student understanding and achievement in PAI subjects. These findings indicate the important role of the dormitory environment and the development of religiosity in improving the quality of Islamic religious education in boarding schools.